Searching for an improvement oral health of the elderly : Is a reform of GES-60 needed? - Valenzuela, M. Josefina (Revista Chilena de Salud Pública, 2015)
In the coming years, Chile will become the Latin American country with the highest prevalence of elderly people. The Explicit Health Guarantees program of integral oral health in persons aged 60 or older (GES-60) guarantees care and treatment for this age group. However, coverage of the program and usage of its services is low. This article raises a number of hypotheses to explain this phenomenon, and proposes an intervention strategy in order to increase coverage, thus improving rates of oral health and quality of life for these individuals